Heavy drinking in men and women in Honduras: a secondary analysis of the Endesa 2019. - Cárcamo-Zepeda, Eduardo; Arturo Valdés-Méndez, José; Torres-Guffanti, Aylin; Valencia, Pablo D.; Cruz-Caraguay, Mishell; Valeria Rivera-Cazaño, Claudia (Salud Pública de México)
Objective. To estimate the prevalence and factors related to heavy drinking in men and women from Honduras. Materials and methods. Data from the 2019 National Demographic and Health Survey were used, and multiple regression models were applied to determine associated factors. Results. 2.8% of men and 0.7% of women incurred in heavy drinking. In men, factors such as age, urban living, having children but not living with them, being people who smoke, and physical assault experiences were associated with a higher likelihood of heavy drinking. For women, higher education levels, urban living, previous marriage or cohabitation, wealth quintile, being people who smoke, and physical assault experiences were linked to a higher prevalence of heavy drinking. Conclusions. The findings provide insight into the issue of excessive alcohol consumption in Honduras and how various experiential, demographic, and health factors may influence its occurrence.